O uso do aço no projeto arquitetônico das estruturas aparente em edifícios de múltiplos andares: uma análise a partir dos projetos em aço construídos nos últimos 20 anos em São Paulo - Magalhães, Wladimir Capelo (2015)
The use of steel structures as building system in multistory buildings is growing every year in Brazil. This evolution, though still slow compared to other countries, is possible thanks to the characteristics of steel and the manufacturing process and production of steel structures. This research paper presents an analysis the use of steel structures in multistory buildings constructed in Sao Paulo in the last 20 years, showing how the use of metal structures was essential to solve the specific problems of each challenge. For this it was essential to understand how metal structures historically evolved since the eighteenth century. From this historical survey, it was possible to establish a series of conditions in the specific use of steel structures that provided its evolution. In addition, there was a survey about the steel industry in Brazil, with an overview of their production, properties, advantages and limitations in order to understand how these characteristics are reflected in the construction of multistory buildings. In the project analysis, seven works were chosen in São Paulo who used the apparent steel structure as the main construction system so that the design adopted confirm structural solutions proposed by architects. To support the analysis, were considered graphics, photos, interviews and three-dimensional electronic models that facilitate the understanding of the structure and elucidate the importance of the use of metal structures. With the results, it was possible to define a set of constraints and determinants of the use of steel in construction that must be considered in the development of architectural design.